HOW INDUCTED IS THE INDUCTED? INDUCTION PROGRAM AND PROFESSIONAL STANDARDS OF PERFORMANCE IN CAPIZ - Almoroto, Rizza Mae; Vasquez, Michael; Dollete, Segundina F (President University, 2025)
This study aimed to assess the level of the induction program and the extent of Professional Standards of Performance in Capiz, addressing a gap in literature within the context of Capiz, other school divisions in the region, and the Philippines. The research employed a mixed-method approach using an explanatory sequential design, with 295 participants and eight focus group discussions (FGDs) involving newly hired teachers in the school's division of Capiz. Quantitative data were collected using a researcher-made questionnaire and analyzed using SPSS Statistics version 26, employing various statistical methods. Qualitative data were analyzed using the descriptive phenomenological approach. The findings revealed that the level of the induction program and the Professional Standards of Performance were